Application of the project method in foreign language teaching in the training of master’s degree students at a non-linguistic university (exemplified by «foreign language in the field of professional communication») - Viktoria G. Grigorieva; Natalia Nazarova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Introduction of new areas of master’s programs in a non-linguistic university sets challenges for foreign language teachers to optimize the language training of the students. The article describes the experience of using a practical-oriented method in teaching the discipline «Foreign Language in the Professional Sphere» to Master’s Degree students of «Management of Museum and Exhibition Activities» at the Samara State Institute of Culture. The preparatory stage of the project activity involved updating the necessary language material based on authentic text and video sources. The next stage was introduction of the Master’s Degree students to exposition and exhibition activities and the latest technologies in museum business on the basis of the Samara «E.A. Ryazanov Museum», which was completed with an excursion conducted by the Master’s Degree students in English. During the next stage, a survey was prepared and carried out among the undergraduate Bachelor students studying museum business on the topic of the project. The final stage of the work was the assessment of the project activities in the form of the participants’ survey regarding the positive impact of the project method on the development of language skills and on the formation of universal and professional competencies.